The First 100 Days as an Academic Department Chair - Dr. Sara Rutledge (Academic Chairpersons Conference Proceedings, 2023)
This session will highlight lessons learned from the presenter’s first 100 days as an academic department chairperson. Topics covered will include: daily operations, faculty, students, alumni, enrollment, retention, academic planning, assessment, accreditation, compliance, governmental relations, articulations, technology, communications, marketing, community engagement, data management, budgeting, reporting, event planning, and initiatives.
Keywords: operations; leadership; communication; collaboration; productivity